Implementation of an Internet-based geographic information system: the Florida experience. - Grigg M; Alfred B; Keller C; Steele JA (Journal of Public Health Management & Practice)
Increasingly, Web-based data dissemination systems are being used to provide public health information. This article describes Florida's experience in augmenting a Web-based data query system, Florida CHARTS, with a geographic information system component. As with any systems development, users' needs guide the product. With a focus on community health assessment and improvement planning, several methods of data display have been established. A variety of issues are explored including the impact of small numbers of events on data display and data confidentiality, the selection of geographic units of analysis, and techniques for geographically coding data.